2012
DOI: 10.1016/j.ijmm.2012.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Does protein phosphorylation govern host cell entry and egress by the Apicomplexa?

Abstract: a b s t r a c tMembers of the phylum Apicomplexa are responsible for a wide range of diseases in humans and animals. The absence of an effective vaccine or safe curing drugs and the continuous emergence of resistant parasites to available treatments impose a high demand on the identification of novel targets for intervention against the apicomplexans. Protein kinases are considered attractive potential therapeutic targets not only against cancers but also to combat infectious diseases. The scope and aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 98 publications
(121 reference statements)
0
21
0
Order By: Relevance
“…In apicomplexan parasites, calcium-mediated signaling plays a major role in a variety of crucial activities, including events that ensure progression in the life cycle such as secretion, gliding mo- tility, and entry into host cells (32), as well as intracellular proliferation, cytokinesis, and stage differentiation (33). Calcium also activates CDPKs, which are found in plants, ciliates, and in apicomplexan parasites but not in mammalian cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…In apicomplexan parasites, calcium-mediated signaling plays a major role in a variety of crucial activities, including events that ensure progression in the life cycle such as secretion, gliding mo- tility, and entry into host cells (32), as well as intracellular proliferation, cytokinesis, and stage differentiation (33). Calcium also activates CDPKs, which are found in plants, ciliates, and in apicomplexan parasites but not in mammalian cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the glideosome is abundantly modified by phosphorylation and acylation in both Toxoplasma gondii and Plasmodium spp. 63 , but site-directed Nature Reviews | Microbiology tachyzoites can be visualized by the trails (shown in green) deposited on a coated surface, which demonstrate circular gliding. The circular motion on a 2D surface is translated into a helical movement in tissues or in a 3D matrigel, and this helical movement can be described as a clockwise corkscrew trajectory that is linked to the left-handed twisted microtubules of the zoite cytoskeleton [99][100][101] .…”
Section: The Glideosome Machinerymentioning
confidence: 99%
“…Micronemes are Ca +2 -regulated secretory organelles that are controlled by phosphorylation-based signaling pathways (reviewed in [11]). Potassium and Ca +2 ion fluxes have been shown to influence parasite motility and egress (reviewed in [12]).…”
Section: Introductionmentioning
confidence: 99%